Islam: Enduring Values for Daily Life (Chicago, IL - August 29 - September 1, 2003) (American Journal of Islam and Society, 2003)
The city of Chicago hosted lSNA's Fortieth Annual Convention, August 29 - September I, 2003, at the huge McCormick Center. In attendance were the ISNA leadership, convention organizers, representatives from major Muslim community and professional organizations, and leaders of other faith groups."We need to be living Islam, but living Islam in the midst of people who may be hostile," said Ingrid Mattson (vice president, ISNA), addressing the session entitled "Morality, Decency and Benevolence: Values that Endure." This panel initiated the convention's theme of "Islam: Enduring Values for Daily Life," based on Qur'an 16:90. Muzammil Siddiqi (former ISNA president) added: "People will know the truth oflslam from the practices of the Muslims." Another theme, closer unity among the monotheistic faiths, was addressed by Talat Sultan (president, ICNA) and Bob Edgar (general secretary, National Council of Churches). Abd Al-Hakim Jackson (professor of Islamic studies, University of Michigan), in the session "Muslims at the Crossroads," stated that Muslims need to become indigenous, without sacrificing Islam, and relate to America as a political arrangement and not a culture. He advised the audience to learn from the African-Americans' experiences. Merve Kavakci, a former Turkish Parliament member who was denied her position because of her hijab, reminded the attendees to practice what they preach, especially when "commanding good and forbidding evil." Azizah Ismail, founder of the Justice Party and wife of Anwar fbrahim, the still-incarcerated former deputy prime minister of Malaysia, related her party's experience, called for the need to eliminate injustice, and said that genuine patriotism is criticizing the country and helping to make it better, but in peaceful and legal ways ...